2007
DOI: 10.4315/0362-028x-70.8.1784
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Salmonella Enteritidis Phage Type 30 from a Single Almond Orchard over a 5-Year Period

Abstract: In 2001, Salmonella Enteritidis phage type (PT) 30 was isolated from drag swabs of 17 61-ha almond orchards on three farms linked to an outbreak of salmonellosis associated with consumption of raw almonds. The objective of this study was to evaluate the long-term persistence of Salmonella Enteritidis PT 30 in one of the almond orchards associated with the outbreak. Swabs (gauze saturated with full-strength sterile evaporated skim milk and attached to string) were pulled along the orchard floor in a standardize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 20 publications
(25 reference statements)
5
60
0
Order By: Relevance
“…Furthermore, the likelihood of pathogen isolation will decrease over time after cultivation, due to exposure to environmental conditions (e.g., UV light) that reduce pathogen loads. This model is supported by previous studies (14,23,42) that have shown the presence and persistence of Salmonella and L. monocytogenes in subsurface soil. For example, Salmonella was detected in 2.6% and 2.0% of soil samples collected from produce-growing regions in California and New York State, respectively, while L. monocytogenes prevalence in soil was 9% in New York State preharvest environments (14,23).…”
Section: Field Practices Associated With Presence Of Pathogenssupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, the likelihood of pathogen isolation will decrease over time after cultivation, due to exposure to environmental conditions (e.g., UV light) that reduce pathogen loads. This model is supported by previous studies (14,23,42) that have shown the presence and persistence of Salmonella and L. monocytogenes in subsurface soil. For example, Salmonella was detected in 2.6% and 2.0% of soil samples collected from produce-growing regions in California and New York State, respectively, while L. monocytogenes prevalence in soil was 9% in New York State preharvest environments (14,23).…”
Section: Field Practices Associated With Presence Of Pathogenssupporting
confidence: 87%
“…Five soil samples per field were taken using sterile scoops (Fisher Scientific, Hampton, NH) at least six inches (15.2 cm) below the surface (subsurface soil) and deposited in separate sterile Whirl-Pak bags (Nasco). A premoistened drag swab (30 ml of buffered peptone water [BPW] [Becton, Dickinson, Franklin Lakes, NJ] in a sterile Whirl-Pak bag), as previously described by Uesugi et al (42), was dragged through the field (side to side in 10-m increments, around perimeter of field) for 10 min. Water samples (n ϭ 74) were collected directly into sterile 250-ml jars; a sampling pole (Nasco) was used if necessary (i.e., for creeks and ponds).…”
Section: Methodsmentioning
confidence: 99%
“…In one study, none of the specimens from wild mice trapped in a major produce production region in California was positive for Salmonella (34). Similarly, none of the rodents sampled following traceback studies carried out after an almond-associated Salmonella outbreak in California was positive for the pathogen (35), underscoring the potentially low occurrence of the organism in rodents in this region of California.…”
Section: Discussionmentioning
confidence: 99%
“…Outbreak-related cases were identified from November 2001 to July 2001 in several provinces across Canada and in several regions in the United States (13). During the traceback investigation, almond retailers, processors, and growers were identified, and S. Enteritidis PT30 was cultured from almond samples, a huller/sheller facility, and environmental samples from the orchards (30). The ability to identify the contaminated food source for this outbreak was aided significantly by the previously rare occurrence of S. Enteritidis PT30.…”
mentioning
confidence: 99%